Inventory of Large Mammal Species in the Ilgaz Mountains Çankırı : A Major Ecological Corridor in Anatolia - Safak Bulut; Burak Akbaba (Hittite Journal of Science and Engineering, 2020)
I n order to understand the processes engendered by different faunal elements in natural systems, and to plan how such systems should be managed and conserved, it is essential to start by determining the presence of those faunal elements, even large mammals. The entire range of North Anatolian Mountains provides suitable sheltering and feeding habitats for large mammals. The region stretching between Köroğlu Mountains west and Ilgaz Mountains east is one of the most important Anatolia’s wildlife corridors. We located and identified the species of large mammals in the Ilgaz Mountains, as well as specific habitats used by them. Field studies carried out in this region during April-August 2017 resulted in 180 records of nine different species of large mammals: Lepus europaeus, Ursus arctos, Canis lupus, Vulpes vulpes, Lynx lynx, Meles meles, Sus scrofa, Cervus elaphus and Capreolus capreolus. To obtain those records took 621 days of studying with camera traps. Among those species, European hare was the most frequently recorded herbivore 101 , and brown bear was the most frequently recorded carnivore 19 . Both hare and roe deer displayed clustered distribution patterns in the region. The analysis of our records showed that lynx, boar, and fox were strictly nocturnal; whereas hare and wolf were predominantly nocturnal. We also obtained records of the cubs of many large mammal species bear, lynx, boar, red deer, roe deer although we did not encounter any large mammal nests during the study